ACTIONS TO OPTIMIZE RECEIVABLES OF THE ENERGY COMPANY - Smyshlyaeva, E.G (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The tasks of optimizing accounts receivable and payable in the power industry are still relevant today. If the utility has overdue accounts receivable, it leads to an unstable working situation in its operations. However, the interconnected management of accounts receivable and payable is still little researched today. Optimization of accounts receivable and payable is perceived as the foundation of a company's cash flow management. At the same time, accounts receivable and payable are considered an indicator reflecting the economic security of an enterprise. In today's economic conditions, there is a "time lag" between different subjects of the energy market from the moment of receipt of payment documents and the date of their actual payment. Accounts payable and receivable show the features of the current system of settlements between companies. In general, the financial activity of energy companies is based on a constant circulation of advanced capital, which is used to purchase means of production, organize production and sell products. It is assumed that in each cycle of a business transaction, these sums of money in the future should provide profit to the enterprise, and therefore - be renewed. Therefore, it is very important to develop measures to help optimize the company's debt, which, in turn, will guarantee its stable financial position.